The effect of psychological first-aid virtual education on the communication skills of nurses in disasters: a randomized controlled trial - Sayed Mohammad Sadegh Madani; Ali Bahramnejad; Zahra Farsi; Azizeh Alizadeh; Maryam Azizi (BMC Psychology, 2024)
Abstract Background Disasters have affected the physical and mental health of people around the world. Since nurses are frontlines in disasters, it seems necessary to prepare for this responsibility. This study investigates the effect of psychological first-aid virtual education on the communication skills of nurses in disasters such as COVID pandemic. Methods In a randomized controlled trial, 55 nurses were selected by purposive sampling method from two hospitals in Isfahan and Tehran, Iran in December—November 2022 and randomly replaced in the intervention group who participated in psychological first aid virtual training and control group. The data were collected through the personal information form and Communication Skills –Test-Revised (CSTR). Results Two groups were homogeneous in terms of communication skills (p = 0.177), the total score of communication skills was significant between the two groups after the intervention (p < 0.0001). Regarding communication skills, in the pre-intervention phase, the subscale of “the ability to receive and send messages” and “insight into the communication process” the difference before the intervention was not significant between the two groups (p > 0.05). However, it was significant between the two groups after the intervention (p < 0.05), and regarding “emotional control”, “listening skills”, and “communication along with assertiveness” the difference before and after the intervention was not significant between the two groups (p > 0.05). Conclusion Pre-disaster training and virtual education can increase nurses’ communication skills in their ability to handle a disaster such as COVID pandemic. Virtual education of post-disaster psychological interventions is suggested. Trial registration IRCT20220923056023N1; date: 2023–01-31.